A study on using portfolio assessment to motivate 9th form students at Nam Hai lower secondary school to learn English - Nguyễn, Thị Hạnh (University of Languages and International Studies, 2017)
This study examines the feasibility of using portfolio assessment to motivate grade nine students to learn English at Nam Hai lower secondary school. The study was implemented on a class of thirty-eight students.